Wellness in the workplace : how to plan, implement and evaluate a wellness program - Sherman, Merlene T. (Crisp Pub. Los altosUS, 1990)
Provides a treasury of health promotion ideas. Shows how to develop and maintain jobsite wellness programmes with practical, low-cost techniques. Also provides rationale for the programmes, and outlines an evaluation procedure.